PERSEPSI KONSUMEN DI KALANGAN MAHASISWA DAN MASYARAKAT UMUM TERHADAP PONSEL PINTAR MEREK BLACKBERRY DI YOGYAKARTA - Azhar Adabi; Hendro Setyono (Jurnal Fokus Manajemen Bisnis, 2012)
This study titled consumer perceptions among students and the general public against the Blackberry smart phone brand in the Jogjakarta. This study aims to determine whether there are difference among students in the consumer and the general public on smart phones. The research was conducted in Yogyakarta inÂ  particular by using a questionnaire, each of 50 respondents who were sampled. By using the technique of sampling, snowball sampling. Analysis of test data used in the arithmetic mean statistic. From the survey results revealed that consumer perceptions of brand smart phone blackberry is positive, where the perception among students is better than the consumerâ€™s perception among the general public. From the analysis of hypothesis testing concluded that the probability of > significance () means there is no difference among students in the consumer and the general public on blackberry smart phone brand. The price of smart phone based on the attribute probability value 0.540. While the quality attributes of a smart phone probability value of 0.149. And attribute value of the probability models of smart phones 0.638